Efficacy of supplementation of a phytase-producing bacterial culture on the performance and nutrient use of broiler chickens fed corn-soybean meal diets - Lan, G.Q.; Abdullah, N.; Jalaludin, S.; Ho, Y.W. (Poultry Science Association, 2002)
We evaluated the efficacy of supplementation of active Mitsuokella jalaludinii culture (AMJC) on the growth performance, nutrient use, and mineral concentrations in tibia bone and plasma of broiler chickens fed corn-soybean meal diets. Dietary treatments included low-nonphytate P (NPP) feed (containing 0.24% and 0.232% NPP for chicks from 1 to 21 and 22 to 42 d of age, respectively), low-NPP feed added with different levels of AMJC (equivalent to 250, 500, 750, and 1,000 U phytase/kg of feed), and normal-NPP feed (containing 0.46 and 0.354% NPP for chicks from 1 to 21 and 22 to 42 d of age, respectively). Supplementation of AMJC to low-NPP feed increased (P < 0.05) weight gain and feed intake and decreased (P < 0.05) feed:gain ratio of chickens during the whole experiment (Days 1 to 42). Supplementation of AMJC increased (P < 0.05) the AME value, digestibility of DM and CP, and retention of P, Ca, and Cu. Mn retention in broilers was only increased (P < 0.05) by AMJC supplementation from 18 to 20 d of age, and Zn retention was improved (P < 0.05) only at a high level of AMJC (equivalent to 1,000 U phytase/kg of feed) supplementation. Chicks fed low-NPP feed added with AMJC had similar tibia ash percentages as those fed the normal-NPP diet. Generally, supplementing AMJC to low-NPP feed increased (P < 0.05) Ca, decreased significantly (P < 0.05) Mn and Cu, but did not affect Zn and P concentrations in tibia ash. Supplementing AMJC also increased (P < 0.05) plasma P but had no effect on plasma Ca or Mn. Plasma Zn concentration was increased only when a high level of AMJC (equivalent to 1,000 U phytase/kg of feed) was used. In conclusion, AMJC supplementation to low-NPP feed improved growth performance; AME value; digestibility of CP and DM; use of Ca, P, and Cu; and bone mineralization.